The robot revolution - Logsdon, Tom (Simon and Schuster, 1984)
In a factory on the slopes of Mount Fuji, industrial robots are now making more robots, working flawlessly around the clock with virtually no human supervision. In Beverly Hills, a robot which normally serves drinks at parties is arrested for handing out business cards illegally in a busy downtown street. From forbidding lunar landscapes to mineral-rich ocean floors, robots perform tasks we thought only humans could do-or could not be done at all. In The Robot Revolution, noted author and computer engineer Tom Logsdon reveals the fact-is stranger than fiction world of robots and the impact they are having in all facets of society, from industry and defense to sports and entertainment. He explores their history from the legendary creations of the ancient Greeks to the experimental ultra sensitive machines of today. And he explains just what robot is and why the latest advances in such fascinating fields as artificial intelligence are making real robots more and more similar to R2D2 and C3P0. Ready or not, The Robot Revolution is here and our lives are never going to be the same again.